2018
DOI: 10.1002/ange.201808586
|View full text |Cite
|
Sign up to set email alerts
|

Ein N‐heterocyclischer Carbenkomplex des Silbers für die plasmaunterstützte räumlich getrennte Atomlagenabscheidung dünner Silberschichten bei Atmosphärendruck

Abstract: Ein Silberamidkomplex eines N‐heterocyclischen Carbens, (1,3‐Di‐tert‐butyl‐imidazolin‐2‐yliden)silber(I)‐1,1,1‐trimethyl‐N‐(trimethylsilyl)silanamid [(NHC)Ag(hmds)], wurde synthetisiert, mittels Einkristall‐Röntgenstrukturanalyse, 1H‐ und 13C‐NMR‐Spektroskopie und EI‐Massenspektrometrie analysiert, sowie bezüglich seiner thermischen Eigenschaften untersucht. Diese neue halogen‐ und phosphorfreie Vorstufe für die Atomlagenabscheidung (ALD) wurde in einem plasmaunterstützten räumlich getrennten (APP‐)ALD‐Prozess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…reflected by a shift of most of the datapoints from similar Cu and Ag complexes at around 0.2 Å, irrespective of the second coordinated atom type X and was further confirmed in our previous studies. [31,32] The complexes synthesized in this study feature CÀ M and CÀ O bonds that can be considered on the shorter end compared to literature known CÀ MÀ O bond lengths. Especially for Ag complexes, shorter and thus stronger bonds might be obtained for N-coordinating anionic ligands indicated by a minimum bond length of 1.95 Å for the shortest MÀ N bond length reported in the CSD and thus should leave room for the optimization of the ligand architecture in the respective complexes.…”
Section: Chemistry-a European Journalmentioning
confidence: 86%
See 2 more Smart Citations
“…reflected by a shift of most of the datapoints from similar Cu and Ag complexes at around 0.2 Å, irrespective of the second coordinated atom type X and was further confirmed in our previous studies. [31,32] The complexes synthesized in this study feature CÀ M and CÀ O bonds that can be considered on the shorter end compared to literature known CÀ MÀ O bond lengths. Especially for Ag complexes, shorter and thus stronger bonds might be obtained for N-coordinating anionic ligands indicated by a minimum bond length of 1.95 Å for the shortest MÀ N bond length reported in the CSD and thus should leave room for the optimization of the ligand architecture in the respective complexes.…”
Section: Chemistry-a European Journalmentioning
confidence: 86%
“…Especially for Ag complexes, shorter and thus stronger bonds might be obtained for N-coordinating anionic ligands indicated by a minimum bond length of 1.95 Å for the shortest MÀ N bond length reported in the CSD and thus should leave room for the optimization of the ligand architecture in the respective complexes. A comparison between the CÀ MÀ O bond angles in Cu and Ag complexes reveal that the coordination is preferentially linear (180°, e. g., [Cu( tBu NHC)(hmds)]), [30,31,33] orthogonal (90°, e. g., [Cu(hmds)] 4 ) or in-between (135°, multidentate or bridged complexes). [40] For Cu, the bond angles for complexes in this study and complexes found in the literature with CuÀ O bonds at short CÀ Cu bond distances below 1.9 Å are highly localized around 180°and 135°, whereas for the parent Ag complexes the bond angles are more distorted and diffuse especially for CÀ Ag bond distances greater than 2.1 Å.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
See 1 more Smart Citation
“…reflected by a shift of most of the datapoints from similar Cu and Ag complexes at around 0.2 Å, irrespective of the second coordinated atom type X and was further confirmed in our previous studies. [31,32] The complexes synthesized in this study feature CÀM and CÀO bonds that can be considered on the shorter end compared to literature known CÀMÀO bond lengths. Especially for Ag complexes, shorter and thus stronger bonds might be obtained for N-coordinating anionic ligands indicated by a minimum bond length of 1.95 Å for the shortest MÀN bond length reported in the CSD and thus should leave room for the optimization of the ligand architecture in the respective complexes.…”
Section: Chemistry-a European Journalmentioning
confidence: 88%
“…Especially for Ag complexes, shorter and thus stronger bonds might be obtained for N-coordinating anionic ligands indicated by a minimum bond length of 1.95 Å for the shortest MÀN bond length reported in the CSD and thus should leave room for the optimization of the ligand architecture in the respective complexes. A comparison between the CÀMÀO bond angles in Cu and Ag complexes reveal that the coordination is preferentially linear (180°, e. g., [Cu( tBu NHC)(hmds)]), [30,31,33] orthogonal (90°, e. g., [Cu(hmds)] 4 ) or in-between (135°, multidentate or bridged complexes). [40] For Cu, the bond angles for complexes in this study and complexes found in the literature with CuÀO bonds at short CÀCu bond distances below 1.9 Å are highly localized around 180°and 135°, whereas for the parent Ag complexes the bond angles are more distorted and diffuse especially for CÀAg bond distances greater than 2.1 Å.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%